ANALISIS LOYALITAS DAN PRODUKTIVITAS PENGURUS ORGANISASI GERAKAN MAHASISWA KRISTEN INDONESIA CABANG MANADO - Valentino R.N. Pakasi; Victor P.K. Lengkong; Jacky S.B. Sumarauw (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to analyze the loyalty and productivity of board members of the GMKI Manado Branch. A qualitative approach using the phenomenological method was employed to explore the experiences, motivations, and challenges faced by the board members in fulfilling their organizational roles. Data were collected through in-depth interviews, observation, and documentation with six key informants. The findings indicate that board members’ loyalty is reflected in their commitment, sense of belonging to the organization, and willingness to dedicate time and energy for the progress of GMKI. Meanwhile, their productivity is influenced by inspirational leadership, a supportive organizational culture, and enviromental support. This study also reveals that the main challenge faced by board members is managing the conflict between academic responsibilities and organizational duties. This research contributes theoretically by enriching the literature on human resource management in faith-based student organizations and provides practical implications for developing future policies on leadership regeneration and organizational management within GMKI.